82.0k views
4 votes
F(x)=8−4x−x^3

g(x)=x^2+7x−9

Find f(x)+g(x).

Select one:
a. x^3+x^2+3x−1
b. −x^3+x+3x−1
c. −x^3+x^2+11x−9
d. 8x^2+3x−9x^3

2 Answers

2 votes

Answer:

its answer is -x^3+x^2+3x-1

Explanation:

f(x) +g(x)

= 8-4x-x^3+x^2+7x-9

= -x^3+x^2+3x-1

User Aizzat Suhardi
by
6.2k points
5 votes

Answer:

The value of f(x)+g(x) is
-x^3+x^2+3x-1.

Explanation:

The given functions are


f(x)=8-4x-x^3


g(x)=x^2+7x-9

We have to find the value of f(x)+g(x).


f(x)+g(x)=(8-4x-x^3)+(x^2+7x-9)


f(x)+g(x)=8-4x-x^3+x^2+7x-9

On combining like terms we get


f(x)+g(x)=-x^3+x^2+(-4x+7x)+(8-9)

On simplification we get


f(x)+g(x)=-x^3+x^2+3x-1

Therefore the value of f(x)+g(x) is
-x^3+x^2+3x-1.

User Vikram Ray
by
5.8k points